Implementasi Aliran Filsafat Perenialisme Dalam Pendidikan Islam - Ezi, Hezi Jeniati; Deriwanto, Deriwanto (Yayasan Literasi Kita Indonesia, 2023)
This study aims to determine how the implementation of perennialism philosophy in the world of Islamic education. Where the relationship between perennialism and education is based on ontological beliefs, where perennialism emphasizes how an educator behaves and recognizes strategies in schooling. Because the essence of this perennialism stream is trying to restore cultural values that have been embraced in the previous era. This type of research is bibliographic, the data collected in this study are two types of data, namely primary data and secondary data. Data obtained from library research (library research). The data collection technique used by this researcher is library research. The data analysis technique in this study uses qualitative analysis techniques by deductive means. The results obtained are that the concept of perennialism has existed since the times of historical and medieval philosophers. Likewise in education subjects, the concept of perennialism in an educational environment is completely based on Plato's philosophy as the father of classical idealism, Aristotle's philosophy is the father of classical realism. Perennialism is a school that originates from the highest truth value, namely the truth from the Most True, namely God, therefore in discussing schools whose main goal is reality, facts, values that are consistent, and timeless.